Boundedness of n-Multiple Discrete Hardy Operators with Weights for 1<q<p<∞ - Aigerim Kalybay; Ryskul Oinarov; Ainur Temirkhanova (Journal of Function Spaces and Applications)
We find necessary and sufficient conditions on weighted sequences ωi, i=1,2,…,n-1, u, and v, for which the operator (Sn-1f)i=∑k1=1i‍ω1,k1⋯∑kn-1=1kn-2‍ωn-1,kn-1∑j=1kn-1‍fj,i≥1, is bounded from lp,v to lq,u for 1<q<p<∞.